Archaeological surveys and their importance in respect of northern sri Lanka - Sajitharan, S. (South Eastern University of Sri Lanka, 2022)
Archaeological studies, historical literature and archaeological heritage confirm that Northern Sri Lanka has an ancient and continuous history of no less than 2,500 years. The Pāli sources which recorded the history of Sri Lanka do not provide a balanced record of the history of all the regions of Sri Lanka in an equal manner. However, Northern Sri Lanka has been mentioned as "Nāgadīpa (m)" since the ancient time and as "Nāgadīpam" and afterwards as "Uttara - desa" since the 7th Century A.D. Archaeological and literary sources state that Northern Sri Lanka was uniquely denoted as "Nāgadīpa(m)" and afterwards as "Uttara - desa" even before the common era i.e. B.C. Confirming this further, a gold plate inscription belonging to the 3rd-4th centuries, found at Vallipuram in 1936, speaks of a Buddhist Vihara found at "Nakātiva" and confirms that the pāli literature was identified as the Nāgadīpa (m) of Northern Sri Lanka. Thus, Northern Sri Lanka referred as "Nāgadīpa (m)" in Pali and "Nāgativa" in Prakrit was identified as "Nākapūmi" and "Nāganatu" which is proved by the archaeological sources and literatures of īlam and Tamil Natu. These sources show that names such as Nāgadīpa (m), Nākapūmi, and Naganātu were used to identify Northern Sri Lanka until 13th century. Accordingly, this study reveals the importance of archaeological studies carried out in Northern Sri Lanka (Nāgadīpa (m)), a region with its unique traditional history since ancient times in the history of Sri Lanka. Therefore, the hypotheses of this study stresses on the importance of archaeological excavations carried out so far in Northern Sri Lanka in understanding the history of Sri Lanka and whether major archaeological studies in Northern Sri Lanka have reread the history of Sri Lanka. The primary objective of the research that is based on the afore mentioned hypothesis, is to study the importance of the archeological excavations carried out here so far in revealing the ancient history of Northern Sri Lanka or in allowing the history of Northern Sri Lanka to be redefined. It further focuses in identifying the role of Northern Sri Lanka in the history of archaeological research of Sri Lanka. In order to fulfill these research objectives, the study has taken the research reports, articles and books published based on the archaeological research conducted in the said area as the primary sources, while data collected through observation of the archaeological sites and archaeological evidences are treated as as secondary data, and thereby the primary and secondary data has been considered in the analysis.
Keywords: Archaeological surveys; Archaeological sites; Archaeological evidences; Megalithic culture; Mesolithic culture